Diversity within Italian Cheesemaking Brine-Associated Bacterial Communities Evidenced by Massive Parallel 16S rRNA Gene Tag Sequencing - Marino, Marilena; Innocente, Nadia; Maifreni, Michela; Mounier, Jérôme; Cobo-Díaz, José F.; Coton, Emmanuel; Carraro, Lisa; Cardazzo, Barbara (Frontiers in Microbiology, 2017)
This study explored the bacterial diversity of brines used for cheesemaking in Italy, as well as their physicochemical characteristics. In this context, nineteen brines used to salt soft, semi-hard, and hard Italian cheeses were collected in fourteen commercial cheese plants and analyzed using a culture-independent amplicon sequencing approach in order to describe their bacterial microbiota. Large NaCl concentration variations were observed among the selected brines, with hard cheese brines exhibiting the highest values. Acidity values showed a great variability too, probably in relation to the brine use prior to sampling. Despite their high salt content, brine microbial loads ranged from 2.11 to 6.51 log CFU/mL for the total mesophilic count. Microbial community profiling assessed by 16S rRNA gene sequencing showed that these ecosystems were dominated by Firmicutes and Proteobacteria, followed by Actinobacteria and Bacteroidetes. Cheese type and brine salinity seem to be the main parameters accountable for brine microbial diversity. On the contrary, brine pH, acidity and protein concentration, correlated to cheese brine age, did not have any selective effect on the microbiota composition. Nine major genera were present in all analyzed brines, indicating that they might compose the core microbiome of cheese brines. Staphylococcus aureus was occasionally detected in brines using selective culture media. Interestingly, bacterial genera associated with a functional and technological use were frequently detected. Indeed Bifidobacteriaceae, which might be valuable probiotic candidates, and specific microbial genera such as Tetragenococcus, Corynebacterium and non-pathogenic Staphylococcus, which can contribute to sensorial properties of ripened cheeses, were widespread within brines.